Asosiasi Pelopor Paguyuban Petani dan Pedagang Tembakau Madura (P4TM) dalam Meningkatkan Pendapatan Petani Tembakau Madura - Shalehoddin, Shalehoddin; Chair, Wasilul; Islam, Muhammad Reza Nurul (Al-Amien Prenduan for Islamic Institute, 2023)
The long flow of the tobacco supply chain means that farmers cannot directly sell their tobacco products to factories directly, and in the supply chain there are naughty elements who often harm farmers. This research aims to obtain complete, comprehensive, meaningful data about the existence of P4TM, then to determine the position and maximize the income of tobacco farmers in Madura. This type of research is qualitative research and uses a phenomenological approach through primary and secondary data sources. With research results; The formation of the P4TM association was due to four problems that caused farmers' anxiety about the future of Madura tobacco. BASSRA (Madurese Ulama Friendship Agency) asks tobacco trade actors in Madura, especially local cigarette factories, to form a farmers' association, P4TM just to act as a pressure group for resolving problems in the tobacco trade system. P4TM held hearings on government officials, stackhoders. Then educate farmers, such as pilot projects, how to buy by paying for samples, and planting seeds and harvesting well. The income of farming communities has increased since the formation of P4TM.